Post-Embryonic Development of Larvae of the Weaver Ant Camponotus textor (Hymenoptera: Formicidae) - Zara, Fernando Jose [UNESP]; Bution, Murillo Lino [UNESP]; Caetano, Flávio Henrique [UNESP] (California State University, 2010)
The post-embryonic development of Camponotus textor is a crucial phase for the colony, since the nest is built with larval silk. Larvae of C. textor (n=200) were randomly collected from the nest, and head capsules were measured, and prepared for SEM. The body presents the pogonomyrmecoid shape and it is covered with three different types of hair. The head structure, with clypeus concave, labrum, mandible and labium are shown in this study. Three morphological patterns were identified during the post-embryonic development. In the third pattern the opening of the gland becomes wider for silk spinning and the praesaepium is no longer present. Some pre-pupa characteristics are already present such as leg vestiges in the mesothoracic region and gonopod vestiges in the posterior region. These larvae stop feeding and the anus becomes terminal in response to to Meconium discharge at the beginning of the pupation phase.
Keywords: weaver ant; SEM; larval instars; silk nest; Camponotus